IMPLEMENTASI BLUE ECONOMY DAN SUSTAINABLE DEVELOPMENT GOALS NO. 14 PADA WISATA CAMPEDAK ISLAND - Wong, Yi; Isa Alamsyahbana, Muhammad; Chartady, Rachmad; Marlinda, Charly; Utami, Ranti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The aim of this study is to find out the implementation of the Blue Economy and Sustainable Development Goals No. 14 on Cempedak Island. The Blue Economy aims to achieve economic and social benefits while maintaining the sustainability of the marine environment in the long term, while Sustainable Development Goals No. 14 focus on sustainable management of marine biological diversity, reduction in marine pollution, sustainable fisheries resource management, and environmentally friendly and sustainable marine development. The method used in this research is qualitative. Data collection is done in two ways: by interview and by library study. Where the informant answers questions that have been prepared by the author based on research indicators. Data processing techniques in this study include performing checks and corrections, performing re-reviews, and providing an explanation of the results of the research carried out. The results of this study show that the implementation of the blue economy based on four (four) indicators in total has been implemented in the activity, but there is one (one) indicator that is still in the trusting phase, namely multiple revenue, where the author does not get information on such matters. Implementation of Sustainable Development Goals No. 14 as a whole has been implemented through activities and work programs since Cempedak Island is a member of the Long Run Alliance Member (LRAM), which is committed to achieving sustainability 4C, namely conservation, community, culture, and commerce. Based on the results of interviews in this study, it can be concluded that the implementation of the Blue Economy and Sustainable Development Goals No. 14 on island tourism has basically been well implemented. But there are indicators of the blue economy that are still in the credibility phase.